2003
DOI: 10.5194/angeo-21-1217-2003
|View full text |Cite
|
Sign up to set email alerts
|

Ulysses COSPIN observations of cosmic rays and solar energetic particles from the South Pole to the North Pole of the Sun during solar maximum

Abstract: Abstract. In 2000-2001Ulysses passed from the south to the north polar regions of the Sun in the inner heliosphere, providing a snapshot of the latitudinal structure of cosmic ray modulation and solar energetic particle populations during a period near solar maximum. Observations from the COSPIN suite of energetic charged particle telescopes show that latitude variations in the cosmic ray intensity in the inner heliosphere are nearly non-existent near solar maximum, whereas small but clear latitude gradients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 32 publications
(35 reference statements)
3
49
0
1
Order By: Relevance
“…The best correlation was found with difference in latitude between the flare site and the latitude of Ulysses, this correlation being surprisingly better than the correlation with the angular separation between the site and Ulysses. This implies a very effective longitudinal transport of the particles, but a very inefficient transport latitudinally, which the authors concluded meant that cross field diffusion was the fundamental mechanism in getting the particles to high latitudes, in agreement with the suggestion by Zhang et al (2003) for the Bastille Day event. However, they did not rule out the possibility that the delay was due to the time taken for the CME to reach the field lines connected to the spacecraft.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…The best correlation was found with difference in latitude between the flare site and the latitude of Ulysses, this correlation being surprisingly better than the correlation with the angular separation between the site and Ulysses. This implies a very effective longitudinal transport of the particles, but a very inefficient transport latitudinally, which the authors concluded meant that cross field diffusion was the fundamental mechanism in getting the particles to high latitudes, in agreement with the suggestion by Zhang et al (2003) for the Bastille Day event. However, they did not rule out the possibility that the delay was due to the time taken for the CME to reach the field lines connected to the spacecraft.…”
supporting
confidence: 70%
“…At high latitudes and in the fast solar wind (70 -80 • N) we found no evidence for any substantial net flow across the field lines, whereas at moderately high latitudes in the slow solar wind (62 • S) Zhang et al (2003) found evidence for cross-field flow.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Comparison of simultaneous SEP observations near the ecliptic plane with the Ulysses observations at high latitudes showed that most events that produce large high-energy (>20 MeV) proton and near-relativistic electron flux increases near Earth also produce flux increases at high latitudes, regardless of the longitudinal, latitudinal and radial separation between the s/c, although with somewhat lower maximum intensities and slower rise at Ulysses (McKibben et al 2003;Lario and Pick 2008;Malandraki et al 2009). Particle anisotropies during SEP events at high latitudes are typically directed outward from the Sun and aligned with the local magnetic field (McKibben et al 2003;Malandraki et al 2009). …”
Section: Multi-spacecraft Observations Of Sep Eventsmentioning
confidence: 99%